2009
DOI: 10.1152/ajpendo.90795.2008
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide sensitive-guanylyl cyclase subunit expression changes during estrous cycle in anterior pituitary glands

Abstract: Cabilla JP, Ronchetti SA, Nudler SI, Miler EA, Quinteros FA, Duvilanski BH. Nitric oxide sensitive-guanylyl cyclase subunit expression changes during estrous cycle in anterior pituitary glands. Am J Physiol Endocrinol Metab 296: E731-E737, 2009. First published January 13, 2009 doi:10.1152/ajpendo.90795.2008.-17␤-Estradiol (E 2 ) exerts inhibitory actions on the nitric oxide pathway in rat adult pituitary glands. Previously, we reported that in vivo E 2 acute treatment had opposite effects on soluble guanylyl … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 28 publications
2
21
0
Order By: Relevance
“…As shown in Figures 3A and 4A and in agreement with previous report [6], free E2 increased α1 and decreased β1 mRNA and protein expression. Unexpectedly, at this time, EDC significantly decreased α1 mRNA and protein expression ( Figure 3A and 4A , respectively), an effect opposite to that seen after 3 h and 6 h of free E2 incubation ( Figure 2 ).…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…As shown in Figures 3A and 4A and in agreement with previous report [6], free E2 increased α1 and decreased β1 mRNA and protein expression. Unexpectedly, at this time, EDC significantly decreased α1 mRNA and protein expression ( Figure 3A and 4A , respectively), an effect opposite to that seen after 3 h and 6 h of free E2 incubation ( Figure 2 ).…”
Section: Resultssupporting
confidence: 93%
“…To investigate which kind of ER is involved in such effect, anterior pituitary cell cultures were incubated with membrane-impermeable E2 compounds: bovine serum albumin-conjugated E2 (E2-BSA) and estrogen dendrimer conjugate (EDC) [25] using the free steroid (E2) as control. First we studied the effect of E2-BSA on α1 and β1 mRNA levels after 6 h of treatment, the same time previously assayed [6]. Our results show that 1 nM E2-BSA was unable to reproduce 1 nM free E2 effects on sGC subunits mRNA expression at the same concentration ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 82%
See 1 more Smart Citation
“…In addition to canonical full-length ␣1 (isoform A) and ␤1 (isoform 2) subunits, three more ␣1 protein isoforms (isoforms B, C, D) and five more ␤1 isoforms (isoforms 1, 3, 4, 5, 6) are predicted to be encoded by these transcripts. Our and other laboratories identified and characterized several sGC splice forms and demonstrated that their expression can modulate sGC function and enzymatic properties in vitro (4,5,7,8,43). These and other studies strongly suggested that alternative splicing of sGC transcripts may be important in regulation of sGC function in vivo.…”
supporting
confidence: 52%
“…The ER mRNA expression is high (Figure 1) in the hypothalamus during GnRH release. GnRH regulates the levels of LH and FSH in the anterior pituitary during estrus in the yak, and estradiol increases soluble guanylyl cyclase in the anterior pituitary at this time (Cabilla et al, 2009). The neuropeptide pituitary adenylate cyclase activating polypeptide is involved in estrus (Moore et al, 2005).…”
Section: Discussionmentioning
confidence: 99%